Analysis of Limited Liability Company Supervision in Indonesia - Ria Veronica; Jeane Neltje Saly (Pusat Publikasi Nusantara, 2023)
This article discusses the supervision of Limited Liability Companies (PT) in Indonesia. PT is a legal entity established through an agreement and conducts business activities with divided capital in the form of shares. The article explains that supervision is carried out to ensure that PT operates in accordance with applicable laws and regulations. PT has characteristics such as separation between the company and its owners, the ability to sue and be sued on behalf of the company, and the right of shareholders to file lawsuits related to ultra vires acts. The article also explains that the requirements for establishing PT in Indonesia have undergone changes, where now PT can be established by one person and can also be operated by one person. The establishment of PT involves providing information such as the company's name, registered address, duration of establishment, purpose and objectives, business activities, capital, shareholders, and founder's data. PT must obtain legal status from the Ministry of Law and Human Rights to be recognized as a legal entity. Failure to obtain approval from the Ministry will result in PT being treated as a partnership or non-legal entity. The Ministry of Law and Human Rights has the authority to revoke the license of PT. Financial and tax supervision of PT is the responsibility of the Ministry of Finance. If the license of PT needs to be revoked, it must go through the Ministry of Law and Human Rights